Performance Analysis of the Milk Pasteurization Process Using a Flat Plate Solar Collector - Surafel Tigabe; Addisu Bekele; Vivek Pandey (Journal of Engineering)
A large share of Ethiopia’s milk production comes from its rural areas. However, this milk does not undergo further processing into dairy products on a large scale due to lack of conventional energy sources such as electricity and gas. Hence, the country is not utilizing its milk resources to the maximum possible. In this study, the possible use of solar energy for the milk pasteurization process is investigated by using a flat plate solar collector (FPSC) with and without reflectors integrated. Reflectors added to the FPSC have augmented the incident solar radiation on the collector from 0.27–0.91 kW/m2 to 0.36–1.18 kW/m2. The thermal efficiency obtained for the FPSC with reflectors integrated is 51.8% whereas that of the collector without reflectors integrated is 46.2%. Likewise, the exergy efficiency is found to be 5.43% for the collector integrated with reflectors and 2.53% for the collector without reflectors. Also, an increase in the daily processed milk production of 18% is observed in September and 16% in November by using the solar collector with reflectors integrated. The quality of pasteurized milk is checked by using the methylene blue reduction test (MBRT) method, and it indicates a better quality of pasteurized milk when compared with raw milk. Therefore, this study shows that the use of solar energy for milk pasteurization has great potential to increase the shelf life of milk, and it can be used as an instrument to improve the quality of life of people living in rural areas.